2017
DOI: 10.1007/s00520-017-3812-7
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for cancer-related fatigue in lung cancer patients: a randomized, double blind, placebo-controlled pilot trial

Abstract: Fatigue is a common symptom experienced by lung cancer patients. Acupuncture may be a safe and feasible optional method for adjunctive treatment in cancer palliative care, and appropriately powered trials are warranted to evaluate the effects of acupuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 34 publications
0
62
0
1
Order By: Relevance
“…Previous studies have focused mostly on the use of haematopoietic growth factors, psychostimulants, dexamethasone, or antidepressants to treat CRF, but the results have been mixed [15][16][17][18]. Alternatively, traditional Chinese medicines, such as acupuncture [19] and herbal extract formula creams, have become a treatment option for Chinese patients. The herbal extract formula cream is widely used for the prevention and treatment of chronic diseases in China [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused mostly on the use of haematopoietic growth factors, psychostimulants, dexamethasone, or antidepressants to treat CRF, but the results have been mixed [15][16][17][18]. Alternatively, traditional Chinese medicines, such as acupuncture [19] and herbal extract formula creams, have become a treatment option for Chinese patients. The herbal extract formula cream is widely used for the prevention and treatment of chronic diseases in China [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture therapy has been successfully used to treat many various diseases for thousands of years. In fact, some research on acupuncture for lung CRF has revealed its advantages [8][9][10], include relieving symptoms, improving patient quality of life and delaying the progression of cancer. However, most of these studies are low value because of some flawed methodology, such as improper treatment times, sample size and lack of blinding.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 , 20 ] These interventions include acupuncture, acupressure, massage, moxibustion, yoga, Qigong, Tai Chi, and neuromuscular electrical stimulation (NMES). [ 21 30 ] Of those, NMES is one of the most potential management for decreasing cancer-related fatigue. However, no data is available to support that NMES can effectively manage this condition, especially specific in patients with ALC.…”
Section: Introductionmentioning
confidence: 99%